2013
DOI: 10.20533/licej.2040.2589.2013.0147
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Learning Culture of High and Low Performing High Schools in Pakistan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 18 publications
(25 reference statements)
0
41
2
Order By: Relevance
“…Studies examined the dimensions of a learning organization in nonprofit organizations (McHargue, ; Watkins et al, ; Wetherington & Daniels, ). Researchers sought to identify the distinctive dimensions of a learning organization in schools (e.g., Akram, Watkins, & Sajid, ; Aydin, Guclu, & Pisapia, ), the army (Stothard, Talbot, Drobnjak, & Fischer, ), or international organizational settings (Watkins, Sadki, Kim, & Suh, 2015).…”
Section: Theories Of the Learning Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies examined the dimensions of a learning organization in nonprofit organizations (McHargue, ; Watkins et al, ; Wetherington & Daniels, ). Researchers sought to identify the distinctive dimensions of a learning organization in schools (e.g., Akram, Watkins, & Sajid, ; Aydin, Guclu, & Pisapia, ), the army (Stothard, Talbot, Drobnjak, & Fischer, ), or international organizational settings (Watkins, Sadki, Kim, & Suh, 2015).…”
Section: Theories Of the Learning Organizationmentioning
confidence: 99%
“…Researchers sought to identify the distinctive dimensions of a learning organization in schools (e.g., Akram, Watkins, & Sajid, 2013;Aydin, Guclu, & Pisapia, 2015), the army (Stothard, Talbot, Drobnjak, & Fischer, 2013), or international organizational settings (Watkins, Sadki, Kim, & Suh, 2015).…”
Section: Dloq Studiesmentioning
confidence: 99%
“…Bai and Fallah (2012) found significant positive correlation between the indicators of learning organization culture and the performance of players in sports. Akram et al (2013) conducted preliminary study on comparing the learning culture of high and low performing boys and girls secondary schools in Pakistan using the DLOQ; this study found that high performing schools demonstrated higher level of learning culture and the vice versa. Bates and Khasawneh (2005) found significant relationships between organizational learning culture, learning transfer climate and organizational innovation in Jordan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If a principal is able to create a learning culture within the school through increasing dialogue and inquiry among teachers, empowering them, and sharing their knowledge, Journal of Education & Social Sciences student achievement might be increased which ultimately helps the principals as well the teachers to meet the accountability standards. Little has been explored about the learning culture in public schools (Akram, Watkins, & Sajid, 2013). One study found positive impact of teacher empowerment on student achievement (Marks & Louis, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Benjamin, 2009;Khan, Tanveer and Saleem, 2013;Nazari and Akmaliah Lope Pihie, 2012;Akram, Watkins and Sajid, 2013;McCharen, Song and Martens, 2011;Ariffin, Hashim and Yahya, 2010). The comprehensiveness of the DLOQ and its proven applicability in various context, cultures and types of organisations (Watkins and Dirani, 2013;Moilanen, 2005), including school organisations, also suggests the value of using the DLOQ in schools.…”
Section: Assessing Schools As Learning Organisationsmentioning
confidence: 99%